Youth on the Move Tendencies and Tensions in Youth Policies and Practices - Brunila, Kristiina; Lundah, Lisbeth (Helsinki University Press, 2020)
This book intends to deepen the knowledge of the extended and uncertain transitions from school to work and to higher education by analysing the perspectives of youths and young adults and by addressing policies and institutional practices. The book critically examines the 'transition machinery' consisting of various education and training measures, projects and schemes, provided by educational institutions, the EU, ministries, municipalities and non-governmental organisations. Treating lack of education and unemployment mainly as individual problems, personal deficiencies or identity issues, the solutions are likewise individualised. The book illustrates how youth transitions are intertwined with social structures, power relations and differences.